The level of communication skill among employees at Kastam Diraja Malaysia, Johor Bahru, Johor / Atirah Nadiah Badrul Zakuan, Hayati Hazana Hamim and Intan Suraya Mohd Lazi - Badrul Zakuan, Atirah Nadiah; Hamim, Hayati Hazana; Mohd Lazi, Intan Suraya (2011)
The purpose of this study was to determine the level of communication skill among employees at Kastam Diraja Malaysia, Johor Bahru, Johor. This study is also hoped to help Kastam Diraja Malaysia, Johor Bahru, Johor improve their operation that includes all criteria in order to satisfy the level of communication skill among employees.In order to obtain the information, a questionnaire was used as the mam instrument. Other than that, information was obtained from primary and secondary data. 60 questionnaires were distributed to the employees at Kastam Diraja Malaysia, Johor Bahru, Johor. The return rates of the questionnaires are 57 (95%). But only 50 (83.33%) results can be used.Based on the findings, the respondents were motivated to improve their knowledge as influenced by the environment in the office. The researchers found that work environment also influence the employees' communication. 70% of the respondents have a high confidence level in their communication because they are frequently communicating with each other in the organization especially about current issues.